ANALISIS KESALAHAN OPERASI DASAR BILANGAN BULAT PESERTA DIKLAT TEKNIS SUBSTANTIF GURU MATEMATIKA MI DI BDK ACEH TAHUN 2018 - Fariha, Mutia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This research is qualitative research with descriptive analysis. The research was gives an overview of the errors made when solving integer basic operations problems. Subjects consisted of 30 people who were participants in the Substantive Technical Training of Madrasah Ibtidaiyah Mathematics Teachers of the Aceh Province in the Balai Diklat Keagamaan Aceh (BDK) in 2018. Data was collected through tests and analyzed to determine the mistakes made by participants in solving problems. Data validation is done by triangulating data sources by comparing test results and interview data on the same subject. The results of the analysis showed that 13 participants (39%) from all subjects still made mistakes in solving problems. The type of error made is a procedure error, namely a sequence of steps in completing a count operation.